Exploring the Misuse of Public-Private Partnerships in Kenya’s Public Procurement: A Study of Governance, Accountability, and Implementation Challenges - Thiga, Henry (Journal of Public Policy and Administration, 2025)
Purpose: The purpose of this study was to explore the Misuse of Public-Private Partnerships in Kenya’s Public Procurement. Methodology: In this research, a qualitative research methodology was adopted, with a focus on desktop research as the main method for data collection. Findings: The study found that Political influence significantly erodes the integrity of PPP procurement processes in Kenya. Often, politicians and government officials leverage their authority to get contracts for firms or individuals that matches with their interests, frequently disregarding the technical and financial qualifications of bidders. The findings also revealed that bribery among other incentives are major concerns in public procurement environment in Kenya, particularly in relation to PPPs. Public officials, as well as those that are involved in procurement, frequently solicit kickbacks from private Companies in return for preferential treatment in contract awards. Lastly, the study revealed that competition is significantly hindered by unclear tendering procedures, selective bidding invitations, and unfair disqualifications of competitors. Unique Contribution to Theory, Practice and Policy: The study provides a unique contribution to the theory, practice, and policy surrounding Public-Private Partnerships (PPPs) in Kenya by highlighting the interplay of political influence, corruption, and institutional shortcomings in procurement processes. The Principal-Agent Theory and Theory of Institutionalism demonstrate how government contracts, intended to be executed transparently and efficiently, often suffer due to favoritism, nepotism, and weak regulatory enforcement. The findings emphasize the need for stronger regulations, transparent tendering procedures, and improved transparency to curb corruption and ensure competition. In practice, this demands reforming procurement laws, bolstering the capacity of oversight institutions, and ensuring a merit-based, transparent process. Policy wise, the study advocates for comprehensive legal reforms, the establishment of digital platforms for procurement management, and the enforcement of anti-corruption laws to foster a fairer, more competitive environment in public procurement, ultimately enhancing public trust and ensuring wise use of public resources.